MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) SEBAGAI PENDEKATAN INOVATIF DALAM PENDIDIKAN DI MADRASAH IBTIDAIYAH - Dulyapit, Apit; Nurmala, Yanti (PGMI UNHASY, 2025)
This study aims to explore the Contextual Teaching and Learning (CTL) model as an innovative approach in education at Madrasah Ibtidaiyah. CTL is a learning model that integrates students' learning experiences with real-life contexts to enhance conceptual understanding and critical thinking skills. The study employs a literature review method by collecting, analyzing, and synthesizing relevant literature. The findings reveal that CTL is effective in creating an active, creative, and meaningful learning environment that aligns with the characteristics of Madrasah Ibtidaiyah students. Furthermore, implementing CTL strengthens the connection between the learning materials and Islamic values taught in madrasahs. This research contributes to the advancement of knowledge by offering an innovative teaching strategy that can improve the quality of Islamic elementary education. The findings are expected to serve as a reference for educators in Madrasah Ibtidaiyah to design more relevant and contextual learning experiences.